Bahasa Indonesia: english - Ricar, Wahyu; Yunisman, Yunisman; Darnetty, Darnetty (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2020)
Controlling Crocidolomia pavonana using an insecticide derived from dishwashing detergents is economical and environmentally friendly. This research was conducted at the Laboratory of Insect Bioecology, Faculty of Agriculture, Andalas University, from November 2019 to March 2020. This study aimed to determine the effect of dishwashing detergent on C. pavonana crop caterpillars. The design used was a completely randomized design (CRD) consisting of 6 treatments and four replications. The treatment given was the application of dishwashing detergent with different concentrations, namely: 0, 0.25%, 0.5%, 1%, 2%, and 4%. The results showed that dishwashing detergent could be used as an alternative insecticide in controlling C. pavonana larvae because it can cause death and give antifeedant effect, but it did not reach the stage of inhibiting larval development. The difference in concentration did not affect the difference in larval mortality. Dishwashing detergent provided a relatively weak antifeedant effect. The higher the concentration, the higher the antifeedant effect. The inhibition of larval development occurred fluctuatively without any particular tendency. Keywords: Crop caterpillar, detergent, soap insecticide, sustainable